Continental‐level population differentiation and environmental adaptation in the mushroom Suillus brevipes. Issue 7 (4th November 2016) - Branco, Sara; Bi, Ke; Liao, Hui‐Ling; Gladieux, Pierre; Badouin, Hélène; Ellison, Christopher E.; Nguyen, Nhu H.; Vilgalys, Rytas; Peay, Kabir G.; Taylor, John W.; Bruns, Thomas D.
Abstract: Recent advancements in sequencing technology allowed researchers to better address the patterns and mechanisms involved in microbial environmental adaptation at large spatial scales. Here we investigated the genomic basis of adaptation to climate at the continental scale in Suillus brevipes, an ectomycorrhizal fungus symbiotically associated with the roots of pine trees. We used genomic data from 55 individuals in seven locations across North America to perform genome scans to detect signatures of positive selection and assess whether temperature and precipitation were associated with genetic differentiation. We found that S. brevipes exhibited overall strong population differentiation, with potential admixture in Canadian populations. This species also displayed genomic signatures of positive selection as well as genomic sites significantly associated with distinct climatic regimes and abiotic environmental parameters. These genomic regions included genes involved in transmembrane transport of substances and helicase activity potentially involved in cold stress response. Our study sheds light on large‐scale environmental adaptation in fungi by identifying putative adaptive genes and providing a framework to further investigate the genetic basis of fungal adaptation.